Insula shows abnormal task‐evoked and resting‐state activity in first‐episode drug‐naïve generalized anxiety disorder. Issue 7 (20th March 2020) - Cui, Huiru; Zhang, Bin; Li, Wei; Li, Hui; Pang, Jiaoyan; Hu, Qiang; Zhang, Lanlan; Tang, Yingying; Yang, Zhi; Wang, Jijun; Li, Chunbo; Northoff, Georg
Abstract: Background: Interoception is associated with neural activity in the insula of healthy humans. On the basis of the somatic symptoms in generalized anxiety disorder (GAD), especially abnormal heartbeat perception, we hypothesized that abnormal activity in the insula was associated with interoceptive awareness in patients with GAD. Methods: We investigated the psychological correlates of interoceptive awareness in a sample of 34 patients with first‐onset, drug‐naïve GAD and 30 healthy controls (HCs). Furthermore, we compared blood oxygenation level‐dependent responses between the two groups during a heartbeat perception task to assess task‐evoked activity and its relationship with psychological measures. We also examined between‐group differences in insular subregions resting‐state functional connectivity (rsFC), and its relationship with anxiety severity. Results: Patients with GAD had significantly higher body perception scores than HCs. They also exhibited greater task‐evoked activity in the left anterior insula, left posterior insula, and right anterior insula during interoceptive awareness than HCs. Left anterior insula activity was positively correlated with body awareness in patients with GAD, and rsFC between the left anterior insula and left medial prefrontal gyrus was negatively correlated with somatic anxiety severity. Conclusions: Investigating a sample of first‐episode, drug‐naïve patients, our study demonstrated abnormal interoceptive awareness in patients with GAD and that this was related to abnormal anterior insular activity during both rest and task. These results shed new light on the psychological and neural substrates of somatic symptoms in GAD, and they may serve to establish abnormal interoceptive awareness as a neural and psychological marker of GAD.